Phaeoisaria yadongensis sp. nov. (Pleurotheciaceae) from Xizang Autonomous Region, China - Li, Ying; He, Shu-Cheng; Li, Cui-Jin-Yi; Yu, Feng-Ming; Luangharn, Thatsanee; Zhao, Qi (Phytotaxa, 2025)
A novel species, Phaeoisaria yadongensis, was isolated from a decaying wood specimen collected from Yadong, Xizang Autonomous Region, China. The species was characterized through a comprehensive evaluation of micro- and macro-morphological features and phylogenetic analyses based on a combination of ITS, LSU, and SSU sequence data. P. yadongensis is distinguished by its parallel, loosely arranged conidiophores that form indeterminate synnemata, denticulate conidiophore cells, and fusiform to ellipsoid conidia containing 1–2 guttulae. Phylogenetic analysis revealed that P. yadongensis forms a sister clade with P. clematidis. However, P. yadongensis can be differentiated from P. clematidis by the length of its indeterminate synnemata, the shape of its fusiform to ellipsoid conidia, and the presence of 1–2 guttulae in its aseptate conidia. The combined morphological and phylogenetic evidence supports the establishment of P. yadongensis as a new species within the genus Phaeoisaria.